The Reception of the Concept of Syura in the Philosophy of Tungku Tigo Sajarangan in Tanah Datar Regency, West Sumatera: (Resepsi Konsep Syura dalam Falsafah Tungku Tigo Sajarangan di Kabupaten Tanah Datar, Sumatera Barat: Studi Living Qur'an) - Yogi Imam Perdana; Satria Tenun Syahputra; Dapit Amril; Yusrizal Efendi (Lembaga Penelitian dan Pengabdian Kepada Masyarakat (LP2M) Sekolah Tinggi Ilmu Al-Qur'an Al Multazam Kuningan, 2026)
This article aims to analyze the acceptance of the concept of shura in the Qur'an in Tanah Datar Regency, West Sumatra. Here, the concept of syura has been adapted into a leadership philosophy called tungku tigo sajarangan. Where did this philosophy originate, and how did the community accept the concept of syura, which was transformed into the tungku tigo sajarangan philosophy? This study uses a qualitative method, with data collected from two sources: literature and field data. Literature data was collected from various references discussing the concept of shura in the Qur'an, while field data was obtained from research subjects in West Sumatra. The method used was a qualitative method with a phenomenological approach and acceptance theory introduced by Ahmad Rafiq as an analytical tool to track informative and performative sources from texts and practices, as well as to observe the process of transmission of a practice and its transformation within society. This study found that the philosophy of tungku tigo sajarangan, which teaches about the deliberation procedure in Tanah Datar, was informatively transmitted from the concept of shura found in QS. Ali Imran [3]: 159 and QS. As-Syura [42]: 38. Performatively, it is transmitted from the form of deliberative practice carried out by the Prophet and his Companions in the books of interpretation and history. Then, the deliberative practice was transformed by the people of Tanah Datar into a philosophy of custom, namely the philosophy of tungku tigo sajarangan.